Evaluation of the performance of clinical predictors in estimating the probability of pulmonary tuberculosis among smear-negative cases in Northern Ethiopia: a cross-sectional study. Issue 11 (3rd November 2020) - George, Mala; Dinant, Geert-Jan; Kentiba, Efrem; Teshome, Teklu; Teshome, Abinet; Tsegaye, Behailu; Spigt, Mark
Abstract : Objectives: To evaluate the performance of the predictors in estimating the probability of pulmonary tuberculosis (PTB) when all versus only significant variables are combined into a decision model (1) among all clinical suspects and (2) among smear-negative cases based on the results of culture tests. Design: A cross-sectional study. Setting: Two public referral hospitals in Tigray, Ethiopia. Participants: A total of 426 consecutive adult patients admitted to the hospitals with clinical suspicion of PTB were screened by sputum smear microscopy and chest radiograph (chest X-ray (CXR)) in accordance with the Ethiopian guidelines of the National Tuberculosis and Leprosy Program. Discontinuation of antituberculosis therapy in the past 3 months, unproductive cough, HIV positivity and unwillingness to give written informed consent were the basis of exclusion from the study. Primary and secondary outcome measures: A total of 354 patients were included in the final analysis, while 72 patients were excluded because culture tests were not done. Results: The strongest predictive variables of culture-positive PTB among patients with clinical suspicion were a positive smear test (OR 172; 95% CI 23.23 to 1273.54) and having CXR lesions compatible with PTB (OR 10.401; 95% CI 5.862 to 18.454). The regression model had a good predictive performance for identifying culture-positive PTB among patients with clinical suspicion (area under the curve (AUC) 0.84), but it was rather poor in patients with a negative smear result (AUC 0.64). Combining all the predictors in the model compared with only the independent significant variables did not really improve its performance to identify culture-positive (AUC 0.84–0.87) and culture-negative (AUC 0.64–0.69) PTB. Conclusions: Our finding suggests that predictive models based on clinical variables will not be useful to discriminate patients with culture-negative PTB from patients with culture-positive PTB among patients with smear-negative cases.